IMPLEMENTASI KURIKULUM 2013 DI TK ANNUR III YOGYAKARTA - Mukhamad Hamid Samiaji; Muidatul Faziyah; Istiningsih Istiningsih; Mohamad Agung Rokhimawan (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2020)
Curriculum is important to note because the curriculum directs all forms and activities of the education process in order to achieve educational objectives. From here, the problem in the research to describe in detail about how implementation planning, the process of implementation of learning with scientific approaches, authentic judgment and how obstacles faced and solutions in implementing the curriculum 2013 PAUD in Annur III TK Yogyakarta.  This type of research is field research with the research object of Annur III TK Yogyakarta. The nature of this research is a descriptive-qualitative that seeks to give an overview of the implementation of existing learning and assessment, to explore the data is done by means of intensive relationship with the data sources of principals, teachers and learning activities. Data in the form of a description of the activity or behavior of subjects and other documents obtained through interviews, observations and documentation. The results showed that: first, planning implementation of curriculum 2013 PAUD in Annur III TK Yogyakarta with the preparation of Semester Program, weekly learning implementation plan, daily Learning Plan, and assessment planning. Secondly, the process of learning with scientific approaches is done during the main step and during the main activities. Thirdly, an authentic assessment process is carried out with daily assessments using data collection techniques, weekly data compilation, monthly data compilation and fourth child Development Report, obstacles faced and solution in implementing PAUD 2013 curriculum in Annur III TK Yogyakarta is a planning format (Prosem, RPPM, RPPH and valuation) that is complicated, scientific approach is only done when learning only, scientific process that is not recorded during play , lack of knowledge in theme sub themes and lack of data processing assessments.